Profiling Preferences of the Counseling Paradigm by School Counselors in Indonesia - Sofyan, Afriyadi; Hidayah, Nur; Ramli, M; Aminah, Siti; Folastri, Sisca (KONSELOR, 2023)
This study aims to obtain an overview of the paradigm tendencies owned and practiced by school counselors in Indonesia. The study involved 233 school counselors in Indonesia on Sumatra, Java, and Bali islands. The research instrument reveals the counseling model that respondents use in providing counseling services (individual/group) and the reasons for its use. Statistics such as frequencies and percentages are used for quantitative data analysis. Qualitative data for reasons for specific counseling models were analyzed using Miles and Huberman data analysis. The results of this study show that school counselors most widely use behavior counseling models because they are effective in overcoming student behavior problems. This approach suits general needs and concerns and is easily understood with its techniques. The rational-emotive behavior therapy counseling model was chosen because it helps change mindsets to be more realistic and mature. This technique follows the needs and problems that arise and the development of adolescents who often act without consideration. Referring to Cotton's opinion, both models are counseling models that fall into the psychological paradigm. The tendency of school counselors to use psychological paradigms may be due to the psychology-focused counselor education curriculum, lack of resources or knowledge of other paradigms, and limitations of the school environment that encourage the use of traditional psychological approaches. School counselors must work with other school staff to integrate counseling approaches into the school program, which is essential. Professional organizations are expected to encourage training in behavioral counseling and REBT, supporting students' holistic education that includes academic, social, and emotional aspects.